KEEFEKTIFAN MANAJEMEN SEKOLAH SD NEGERI MULIA PUNCAK JAYA PAPUA TENGAH - yusri; Sulistyo; farida ni'matullah, onik (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to evaluate the effectiveness of school management in SD Negeri Mulia, Puncak Jaya, Central Papua Province, with a focus on aspects of leadership, curriculum and learning, teaching quality, facilities, financial management, parent participation, student achievement, student welfare, continuous evaluation, and community relations. The research approach used by the researcher is a qualitative approach. Data collection techniques include: observation, interviews, and documentation. Meanwhile, the data analysis technique begins with reducing the data, followed by presenting the data, and finally draws conclusions. The results of the study show that the participatory leadership applied by the principal, Mrs. Maria Wanggai, has succeeded in creating a collaborative work environment, despite budget and infrastructure constraints. The curriculum used is in accordance with national education standards, but its implementation is hampered by limited resources. Teachers are highly committed and experienced, but require more professional training. School facilities, including classrooms, libraries, and computer labs, require repairs and additions to equipment. Financial management is carried out transparently, but the available budget is often insufficient. Parents are actively involved in their children's education and value better communication with the school. The academic performance of students is quite good, especially in the fields of science and mathematics. The health and hygiene program is running well, but some facilities such as toilets need to be improved. Community support is strong, and partnerships with NGOs help in improving educational facilities and programs.